Chemistry for advanced level - Cann, Peter (John Murray, 2002)
Chemistry for Advanced Level aims to provide a clear and thorough explanation of the key concepts required by all the latest A level specifications and highlights ways in which these concepts are applied in the world around us.;Initial chapters start at a level suitable for GCSE Double Award Science students and the text includes numerous worked examples. Further practice questions with answers allow students to test themselves, while extension boxes provide extra information on applications or more detailed coverage of the theory. Each chapter ends with a summary of key facts and ideas and end-of-chapter questions include many taken from past examination papers.